Understanding the Strength of Muslim Identity as a Way to Manage Anxiety and Uncertainty for Foreign Students While Communicate Digitally in the US - Millenia Rizki Ramadita; Muhamad Lutfi Habibi (Kalijaga Journal of Communication, 2023)
This study aims to provide recommendations to foreign Muslim students studying in the United States (US) so they can manage their anxiety and uncertainty when communicating digitally on social media. This research is motivated by the challenges foreign Muslim students face when they have to adapt to interactions that exist in conditions of society that are far different from their origin country, there is not much time, and the scope is now also expanding into the digital world. The method used in this research is qualitative with a case study approach. Data was collected through in-depth interviews based on the Anxiety and Uncertainty Management (AUM) theory by William B. Gudykunst with three foreign Muslim students from Turkey, Morocco, and Pakistan who were studying at Utah Tech University. The research results show that understanding the strength of Muslim identity contained in oneself is one of the most effective ways to reduce the anxiety and uncertainty they often experience. In addition to understanding Muslim identity, other recommendations include using social media to educate people about negative Islamic stereotypes, not giving opinions that conflict with local values, and trying to communicate like US netizens to familiar people. Suggestions for further research are to expand the scope of research by adding more participants from more diverse cultural backgrounds.